1998
DOI: 10.1029/98wr01704
|View full text |Cite
|
Sign up to set email alerts
|

The fate of geothermal arsenic in the Madison and Missouri Rivers, Montana and Wyoming

Abstract: Abstract. Geothermal As from Yellowstone National Park causes high As concentrations (10-370/•g/L) in the Madison and Missouri Rivers in Montana and Wyoming. Arsenic transport is largely conservative in the upper basin as demonstrated by the near equivalence of dissolved and total-recoverable As concentrations, the constancy of As loads, and consistent ratios of concentrations of As to conservative geothermal tracers. Diurnal cycling of As between aqueous and solid phases in response to p H-induced changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(48 citation statements)
references
References 49 publications
2
46
0
Order By: Relevance
“…We hypothesize that reduced stream discharge, especially during summer low flow conditions, will increase the magnitude of effects and spatial extent of geothermal discharges in YNP. Nimick et al (1998) reported that the spatial distribution of geothermal waters and concentrations of associated trace elements in YNP were greatest during low flow conditions. Combined with warmer stream temperatures and reduced dissolved oxygen concentrations, it is likely that effects of geothermal stressors on aquatic organisms will become more widespread as a result of climate change.…”
Section: Potential Effects Of Climate Change On Geothermal Influencesmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that reduced stream discharge, especially during summer low flow conditions, will increase the magnitude of effects and spatial extent of geothermal discharges in YNP. Nimick et al (1998) reported that the spatial distribution of geothermal waters and concentrations of associated trace elements in YNP were greatest during low flow conditions. Combined with warmer stream temperatures and reduced dissolved oxygen concentrations, it is likely that effects of geothermal stressors on aquatic organisms will become more widespread as a result of climate change.…”
Section: Potential Effects Of Climate Change On Geothermal Influencesmentioning
confidence: 99%
“…High water temperature and conductivity, low pH and the input of fine sediments associated with geothermal areas are natural features of these streams. In addition, elevated concentrations of trace elements often co-occur with geothermal discharges (Thompson 1979;Nimick et al 1998;Goldstein et al 2001). Effects of these naturally occurring stressors on macroinvertebrates and fish have been reported in YNP (Armitage 1958;Kaeding 1996;Goldstein et al 2001), Iceland (Castenholz 1969 and New Zealand (Duggan et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic concentrations up to 27 000 μg L −1 in California geothermal waters and 2700-3500 μg L −1 in Nevada and Utah hot springs have been reported (Smedley and Kinniburgh, 2002;Welch, Lico and Hughes, 1988). In the vicinity of the Yellowstone geothermal system in Wyoming, Idaho, and Montana, elevated arsenic concentrations occur in thermal waters (Smedley and Kinniburgh, 2002), in the Madison River (up to 370 μg L −1 ; (Nimick et al, 1998)), and in groundwater of the Madison and upper Missouri River valleys (Welch et al, 2000).…”
Section: Western Usamentioning
confidence: 99%
“…Weathering and erosion of ultramafic rocks has been recognized as a natural source of chromium in sediments and groundwater (Fantoni et al, 2002;Kaprara et al, 2015;Kazakis et al, 2015;Dermatas et al, 2015). The release of arsenic in groundwater can be due to the reductive dissolution of arsenic-bearing iron oxides (Harvey et al, 2002), the released As through sulfide oxidation reactions (Chowdhury et al, 1999) and the result of geothermal inputs (Nimik et al, 1998;Pique et al, 2010). Geothermal fluids circulating through faults can also be a source of As on groundwater and soils (Gamaletsos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%